Network mapping in the development of elephant conservation center in North Sumatra, Indonesia - Rospita Odorlina P Situmorang; Wanda Kuswanda (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Situmorang ROP, Kuswanda W. 2019. Network mapping in the development of elephant conservation center in North Sumatra, Indonesia. Biodiversitas 20: 2858-2867. A project in the Aek Nauli Elephant Conservation Camp (ANECC) is being carried out to conserve Sumatran elephant handled by several institutions within the Ministry of Environmental and Forestry of Republic of Indonesia and other supporting stakeholders. A social networking analysis (SNA) had been carried out to analyze the social interactions of the stakeholders in the development of the ANECC. This research aimed at finding out the important actors in the network and describing at the social network gap in the development of ANECC objectives as conservation, and research, and ecotourism center. From the research, we found four institutions engaged in conservation, research, and animal health surveillance as the core actors and 19 other institutions as the periphery actors consisting of authorities, local government, businessmen, and local people. The study also found that the Environmental and Forestry Research and Development Institute Aek Nauli is the most influential actor in the network, and the National Planning Agency and Girsang Sipanganbolon Sub-district as the bridging actors who connect the supporting actors to the core actors. Conservation aspect is the most communicated in the network, followed by ecotourism, and research. Our research also found that conservation and research aspects have been handled by the appropriate institutions, however, ecotourism has not been handled by certain agencies responsible for the development of ecotourism. Hence, the study suggests that the core actors can consider binding cooperation with potential entrepreneurs on tourism around the site to develop ecotourism sector in ANECC.